RISK FACTORS FOR THE ANEMIA IN PREGNANT WOMEN: A LITERATURE REVIEW - Nurnaningsih Nurnaningsih; Mardiana Ahmad; Isharyah Sunarno; Nur Aliya Arsyad (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: Anemia in pregnancy is still a global public health problem and is the largest contributor to morbidity and mortality. Some studies report that risk factors for anemia vary from place to place, so more in-person observations are needed regarding anemia risk factors. Objectives: This study aimed to determine the risk factors of anemia in pregnant women. Methods of using literature review studies. Design: This study design is a literature review to search and review article from database and the theory which is descriptive. Data Sources: Search for scientific articles using the Mendeley application by entering the keyword